THE EFFECT OF FINANCIAL PERFORMANCE, DIVIDEND POLICY, SALES GROWTH, AND INFLATION ON STOCK PRICES IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017-2020 - fithrotul auliya; Supriyono; Hutomo Rusdianto (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Stock prices in the capital market reflect one of the indicators of a company’s success in managing its company. Stock prices are volatile, meaning they can change over time. Financial performance, dividend policy, and sales growth can influence an investor’s decision to invest capital in stocks. This makes the company’s stock price fluctuate. The purpose of this study is to find out how the current ratio measures financial performance, dividend policy is measured by the DPR, sales growth is measured by sales indicators, and the consumer price index measures inflation can affect the stock price of banking companies listed on the IDX in 2017-2020. The method used was t-test analysis, with a sample of 11 banking companies using the purposive sampling method. The results of this study show that the current ratio measures finance, the DPR measures dividend policy, and sales growth with sales indicators affects stock prices. Inflation with the consumer price index does not affect stock prices.